Influence of the addition of “synthetic termite saliva” in the compressive strength and water absorption of compacted soil-cement - Faria, Obede Borges; Battistelle, Rosane Aparecida Gomes; Neves, Célia (Ambiente Construído, 2016)
The aim of this paper is to determine the effect of adding 0.1 wt% of “synthetic termite saliva” on a fine and clayey sand latosol (76.5% sand) from the region of Bauru, SP (Brazil), stabilized with 1% to 3% of cement. Compacted cylindrical specimens (with standard Proctor energy) were tested to determine their compressive strength and water absorption. The results indicate that the use of the chemical stabilizer increased by at least 35% the compressive strength and reduced by up to 13% the water absorption of the samples. This work contributes to efforts aimed at reducing the consumption of cement through the production of stabilized compressed earth blocks and bricks (CEB) and rammed earth.